Comparison of efficacy and safety of daily oral L‐arginine and PDE5Is alone or combination in treating erectile dysfunction: A systematic review and meta‐analysis of randomised controlled trials. (15th February 2021) - Xu, Zhunan; Liu, Chu; Liu, Shuang; Zhou, Zhongbao
Abstract: The meta‐analysis was performed to assess the efficacy and safety of daily oral L‐arginine and phosphodiesterase type 5 inhibitors (PDE5Is) alone or combination in treating patients with erectile dysfunction (ED). We performed a search of randomised controlled trials in the following databases: PubMed, EMBASE and Cochrane Library databases. Four articles including 373 patients were studied. Erectile functions were significantly improved in three therapy groups compared with baseline. Patients who received the combination of L‐arginine and PDE5Is showed significant improvement compared to those treated with L‐arginine and PDE5Is alone, as assessed by sexual function index ( p  <0.00001 and p  =0.005, respectively) and total testosterone ( p  <0.00001 and p  =0.0007, respectively). Furthermore, patients who treated with PDE5Is alone exhibited the better efficacy than those treated with L‐arginine alone in respects of sexual function index ( p  <0.00001) and total testosterone ( p  =0.0001). However, the combination of L‐arginine and PDE5Is had no obvious difference relative to PDE5Is alone in terms of various adverse events (AEs). Conclusively, compared with monotherapy, the combination of L‐arginine and PDE5Is showed a greater improvement of sexual function and total testosterone, and did not significantly increase the AEs. Besides, PDE5Is alone revealed a better effect than those treated with L‐arginine alone for patients with ED.